Commonality in Tail Risk Premia around the World - Lee, Kuan Hui; Wang, Shu Feng (Korean Journal of Financial Studies, 2023)
This study examines tail risk premia for 44 countries from 1990 to 2015 and provides evidence on the existence of common and systematic components in the variation of tail risk premia across countries. Specifically, we found that individual countries’ tail risk premia significantly comove with U.S., regional, and global tail risk premia. The first five principal components explain all variation in the premia, with the first principal component alone ex-plaining over 30% of the variation. The comovement, or commonality, is stronger for developed market countries and more open countries. We also provide evidence that premia are affected by the U.S. economic environment and global stock market volatility, leading to a common variation in tail risk premia around the world.
Keywords: Commonality; Comovement; International Stock Market; Tail Risk; Tail Risk Premium